Counterradicalism Through Religious Education Curriculum: Solution to The Religious Literacy Crisis in Indonesian Islamic Universities - Sapdi, Rohmat Mulyana; Ali, Nur (TADRIS: Jurnal Pendidikan Islam, 2022)
Islamic universities have been accused of being the milieu of the growing movement of radicalism along with the new facts about the involvement of two state Islamic universities among 10 state universities involved in radicalism. The campus management has responded to the movement by developing a religious curriculum and interreligious-based learning to improve religious literacy competence. This paper aims to evaluative the practice of religious curriculum and literacy as a strategy in improving counterradicalism in campus. The interviews, observations, and data analysis resulted in the finding that the religious curriculum development with open minded principles, religious universality, local wisdom, and humanism values in the learning activities in either classroom and or places of worship of other religions can foster good counterradicalism and interfaith literacy and eliminate the evolution of radical attitudes among students. This paper suggested that the learning of religious education in campuses and schools include observation to the areas of interreligious activities and religious literacy studies to improve students' understanding of religious values among religious communities, so tolerance and counterradicalism can be fostered.